Investigational anabolic agents for the treatment of osteoporosis: an update on recent developments. (3rd October 2017) - Dede, Anastasia D; Makras, Polyzois; Anastasilakis, Athanasios D.
ABSTRACT: Introduction : Teriparatide, a PTH analogue, was the first anabolic agent to be approved for the treatment of osteoporosis in 2002. Abaloparatide was also recently approved by the FDA. The need for other anabolic agents is still unmet. Areas covered : In this review, we discuss target molecules and recent advances in the field of anabolic therapy for osteoporosis. PTH and PTHrP analogues binding to the PTH receptor and different routes of administration of teriparatide to avoid the burden of daily subcutaneous injections are discussed. We also review antibodies targeting suppressors of the Wnt pathway such as sclerostin and Dickopff-1. Expert opinion : The development of alternative ways of administering PTH receptor ligands is a promising field, especially via the transdermal route. Other more promising molecules are still at very early stages of development. FDA recently requested more data on Romosozumab.